Report of 27th International Congrerss of AHML held at Kathmandu, Nepal (Advancements in Homeopathic Research, 2022)
The 27th International Congress of Asian Homoeopathic Medical League was held at Kathmandu, the capital of Nepal on 20th and 21st April 2019 and was organized by the Nepal Chapter of AHML. About 200 delegates hailed from India, Bangladesh, Pakistan, Russia, Kazakhstan, Malaysia and Nepal participated. The former Prime Minister and President of Ruling party (NCP) of Nepal, Sri Pushp Kamal Dahal “Prachand” was the chief guest, Dr. Bishnu Prasad Misra, IPP of All Nepal Homoeopathic Association was the Chairperson and Dr. A. K. Seth, the President of AHML was Guest of Honour. The other dignitaries present on the dais were Hon’ble Sudip Pathak, Central Member of National Human Rights Commission of Nepal; Dr. Kamal Prasad Subedi, President ANHA; Dr. Ravi Prakash Roy, President of Nepal Homoeopathic Chikitsak Sangh; Dr. Dilip Kumar Roy, Vice-President, AHML from Bangladesh; Dr. Girish Gupta, Secretary General, AHML; Dr. Ambika Gyawali, NVP, Nepal Chapter and Dr. Chandra Sharma Dulal, Secretary, Nepal Chapter of AHML.
Keywords: International Congrerss; AHML; Kathmandu; Nepal; (NCP)